Homebuyers' buying behaviour for high rise property in Ipoh - Lum, Wai Yin (2018)
Ipoh is the capital of one of the Malaysia states Perak. It is located by the Kinta River, around 180 km north of Malaysia’s national capital, Kuala Lumpur and 123 km southeast of Penang state. As of 2010, Ipoh has a population of 657,892 people. This makes Ipoh as Malaysia third largest city according to population. Malaysia’s is having a strong growth period in residential housing market. To maintain this flourishing growth, marketers require an in-depth understanding in purchasing behaviours of the buyer. It helps properties suppliers achieving a sustainable competitive advantage. It is crucial to know that the purchaser really wants as buyers are becoming more cautious before getting their houses in order to reduce mismatch in housing provision. Housing developer needs to have detail knowledge on how is Malaysian purchaser differ in perception, preference and option in their choice of houses. Generally, Malaysian prefer gated-guarded landscape compound but there are limited access to the value provided in Ipoh, Malaysia. And because of this problem, the main emphasis of this paper is to determine whether the respondent is willing to pay to changes in neighbourhood types and what are their preferences in selecting one. The purpose of this research is to determine the critical attributes on buyer’s decision in selecting a house in Ipoh, Malaysia and to determine which individual buyers’ characteristics affects their evaluation of housing attributes and their choice in Ipoh, Malaysia. Survey is done in Ipoh and the data will be analyse through descriptive analysis, scale measurement, reliability test, inferential analysis, Pearson correlation coefficient analysis, independent T-test, and also multiple regression analysis. It is found that Ipoh community wanted to own new properties but still not able to accept high rise property and the critical attributes that affect buyer decision is property price.